The Eco-efficiency Index at the international level:: a comparative analysis of the performance of 51 countries between 1991 and 2012 (Sustainability in Debate, 2017)
The objective of this research was to calculate the Eco-efficiency Index (IE) for 51 countries using the Data Envelopment Analysis (DEA) method. It was found that the value of the average eco-efficiency has decreased between the years 1991 and 2012. Developed countries in general, and the European continent in particular, displayed the highest levels of eco-efficiency. Overall, in all years, the EI has been very low in most countries, half of which are developing countries and are located predominantly in the Asian continente. The main implication of this research is that stricter environmental regulations are required, especially for countries that have low eco-efficiency values. This analysis aims to incresase awareness in order to propose more sustainable developement strategies for future generations.